Narrow-Band Imaging in Digestive Endoscopy. (2007) - Lambert, R.; Kuznetsov, K.; Rey, J-F.
Abstract : The application of opto-electronics in video-endoscopes improves the accuracy in diagnosis, through image processing and digital technology. Narrow Band Imaging (NBI), consists of using interference filters for the illumination of the target in narrowed blue and green bands of the spectrum. NBI is combined with magnifying endoscopy using an objective macro or an optical zoom. The NBI technique developed by Olympus Medical Systems is now available in the most recent models of video-endoscopes that use the non-sequential system of illumination (Lucera Spectrum) or the sequential R/G/B system of illumination (Exera II). The major contribution of the technique is in the characterization (analysis after detection) of the flat and superficial neoplastic areas of the digestive mucosa, with a specific application to the identification of intestinal metaplasia and early neoplastic changes in the Barrett's esophagus. The technique also proves helpful for the assessment of the vascular pattern in chronic inflammatory disorders of the digestive mucosa.